P724 Unchanged infliximab serum concentrations after switching from the originator infliximab to the biosimilar CT-P13 in patients with quiescent inflammatory bowel disease: Results from a prospective study (SECURE). (16th January 2018) - Strik, A; van de Vrie, W; Bloemsaat-Minekus, J; Nurmohamed, M; Bossuyt, P; Bodelier, A; Rispens, T; van Megen, Y; D'Haens, G
Abstract: Background: Switching patients from originator infliximab (IFX) to biosimilar IFX can reduce healthcare costs; however prospectively collected data about pharmacokinetics and potential immunogenicity is scarce. The objective of the SECURE (IFX4501) study was to demonstrate the non-inferiority of IFX serum concentrations of biosimilar IFX Remsima® (CT-P13, Celltrion, South Korea) to IFX concentrations of Remicade® (Johnson and Johnson, USA) 16 weeks after switching in patients with inflammatory bowel disease (IBD) and rheumatoid arthritis. This abstract reports the results of the IBD cohort. Methods: In this prospective, open-label, interventional, non-inferiority, multi-centre, phase IV trial, adult patients with Crohn's disease (CD) and ulcerative colitis (UC) in clinical remission at stable dose>30 weeks (HBI ≤4; SCCAI <2.5) were switched from originator IFX to CT-P13. Patients were followed for 16 weeks (2 infusions) after switching. Primary endpoint was the IFX serum trough concentration measured with a bridging enzyme-linked immunosorbent assay 16 weeks after switch. The non-inferiority margin was set at 15%. Secondary endpoints included the IFX serum concentration 8 weeks after switching, antidrug antibodies (ADA), clinical disease activity, biomarkers and quality of life 8 and/or 16 weeks after switching. Results: Between July, 2015 and December, 2016, 120 IBD patients were recruited (59 UC, 61 CD). The per protocol analysis set included 46 (52%) UC patients and 42 (48%) CD patients. In neither indication, the 90% CI of the adjusted risk difference exceeded the pre-specified non-inferiority margin (Table 1). Likewise, no significant changes were observed in biomarker measurements, clinical disease activity and quality of life of patients at 16 weeks after switching. Six SAEs (planned abortion, two perianal abscesses, carpal tunnel syndrome, swollen lymph node, adenocarcinoma appendix) were reported in six patients. At baseline, five out of 88 patients (6%) were ADA positive and in three other patients ADA levels became detectable during follow-up. Conclusions: In this prospective, interventional study, IFX serum concentrations of CT-P13 were non-inferior after switch from originator for UC and CD patients. Likewise, there were no significant changes in clinical and biochemical efficacy, quality of life and tolerability. This study is sponsored by Mundipharma Pharmaceuticals BV.